Edible Film Innovation from Jackfruit Seed Starch (Artocarpus hetrophyllus) with the Addition of Sorbitol and Carrageenan - Putri, Radenrara Dewi Artanti; Fitrianto, Rizqi (International Journal of Research Innovation and Entrepreneurship, 2020)
Edible films are considered as the best alternative as an environmentally friendly and safe food packaging. Edible films could be made from plant-based (e.g. starch, cellulose and lignin) and animal-based (e.g. protein, casein and lipids) starting materials. This study investigated the production of edible films from widely available starch-based materials. In this research, the synthesis of the edible films from jackfruit seed starch was carried out by adding sorbitol as a plasticizer and carrageenan as a biopolymer. Carrageenan was added at various concentrations (0-60 wt.%). Furthermore, the effect of carrageenan concentration on the mechanical properties of the edible films (tensile strength, elongation, and modulus young) was investigated. The prepared edible films were applied on the bananas’ skin to improve the shelf life of the fruit. The edible films with the addition of sorbitol plasticizer and carrageenan biopolymer could affect the tensile strength, elongation and elasticity (modulus young) values of the edible films. The increase in the tensile strength and elasticity of the edible films was observed with increasing carrageenan concentrations. In contrast, the elongation value of the edible films decreased with increasing carrageenan concentrations.